MINERALOGY AND GEOCHEMISTRY OF THE TRIADESGALANA PB-ZN-AG-AU INTERMEDIATE-HIGH SULFIDATION EPITHERMAL MINERALIZATION, MILOS ISLAND, GREECE - Papavasiliou, K.; Voudouris, P.; Kanellopoulos, C.; Alfieris, D.; Xydous, S. (Bulletin of the Geological Society of Greece, 2016)
The Triades-Galana Pb-Zn-Ag-Au mineralization is a shallow-submarine epithermal mineralization located along NE-trending faults, NW Milos Island, Greece. It is hosted in 2.5–1.4 Ma pyroclastic rocks and is genetically related to andesitic/dacitic lava domes. Mineralization occurs as breccias, quartz-barite galena veins and stockworks within sericite-adularia or kaolinitic altered rocks. The mineralization is enriched in Mo, W and base- and precious metals (e.g. Pb, Zn, Ag) similarly to the neighbouring mineralization at Kondaros-Katsimouti and Vani, indicating common source of metals from a deep buried granitoid feeding western Milos with metals and volatiles. Paragenetic relations suggest early deposition of pyrite, followed by famatinite, polybasite and Ag-rich tetrahedrite, and then by enargite, suggesting fluctuating sulfidation states during ore formation. The evolution from Sb- towards As-rich enrichment indicate a renewed magmatic pulse (probably in the form of magmatic gases) in the hydrothermal system. Silver is present in the structure of sulfosalts (up to 66.2 wt.% in polybasite-pearceite, 15.1 wt.% in tetrahedrite and 60 wt. % in pyrargyrite). Boiling processes (as evidenced by the presence of adularia accompanying intermediate-sulfidation ore) and mixing with seawater (presence of hypogene lead chlorides) and contemporaneous uplift, contributed to ore formation.